1998
DOI: 10.1007/bf02386670
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of some natural and anthropogenic radionuclides in Sudanese harbour sediments

Abstract: The distribution of some natural and anthropogenic radionuclides (226p~a, 228Ra, 21~ 4~ 137Cs) in surface marine sediments from the harbours at Port Sudan and Sawakin on the Sudanese coast of the Red Sea has been investigated using a-spectrometry and direct high-resolution ~/-spectrometry. The prime aims were to assess the levels of radioactivity and the influence of factors such as dredging and the organic matter content of the sediments on the distribution pattern of the radionuclides. The results have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Nyarko et al (2011) also reported lower activity concentrations of 210 Pb in beach sand samples along the Ghana coast ranging from 1.6 up to 4.5 Bq kg À1 and 137 Cs concentrations below the detection limit of 0.4 Bq kg À1 . The mean radioactivity levels in the Tema Harbour sediments were also higher than the levels reported for the Mediterranean coast of Egypt (Higgy, 2000), but were comparable to (Sam et al, 1998), Patras Harbour, Greece (Papaefthymiou et al, 2007), Mumbai Harbour, India (Sugandhi et al, 2014), and the Karachi Harbour, Pakistan (Sugandhi et al, 2014). The mean radioactivity levels of 238 U, 232 Th, 40 K and 137 Cs in the Tema Harbour sediments were, however, much lower than those found in polluted sediments from the Caspian Sea coast of Iran (Abdi, Hassanzadeh, Kamali, & Raji, 2009).…”
Section: Concentrations Of Radionuclides In Tema Harbour Sedimentssupporting
confidence: 44%
See 1 more Smart Citation
“…Nyarko et al (2011) also reported lower activity concentrations of 210 Pb in beach sand samples along the Ghana coast ranging from 1.6 up to 4.5 Bq kg À1 and 137 Cs concentrations below the detection limit of 0.4 Bq kg À1 . The mean radioactivity levels in the Tema Harbour sediments were also higher than the levels reported for the Mediterranean coast of Egypt (Higgy, 2000), but were comparable to (Sam et al, 1998), Patras Harbour, Greece (Papaefthymiou et al, 2007), Mumbai Harbour, India (Sugandhi et al, 2014), and the Karachi Harbour, Pakistan (Sugandhi et al, 2014). The mean radioactivity levels of 238 U, 232 Th, 40 K and 137 Cs in the Tema Harbour sediments were, however, much lower than those found in polluted sediments from the Caspian Sea coast of Iran (Abdi, Hassanzadeh, Kamali, & Raji, 2009).…”
Section: Concentrations Of Radionuclides In Tema Harbour Sedimentssupporting
confidence: 44%
“…In the coastal environment, harbours may be particularly susceptible to anthropogenic influences and their sediments can act as sinks for radionuclides (Sugandhi, Joshi, & Ravi, 2014). Harbours have hence been areas of interest when investigating radionuclide contamination in the coastal environment (Akram et al, 2006;Kumar et al, 2013;Papaefthymiou, Papatheodorou, Moustakli, Christodoulou, & Geraga, 2007;Sam, ElGanawi, Ahamed, & ElKhangi, 1998;Sugandhi et al, 2014). Sediment contamination by radionuclides of the 238 U and 232 Th decay-series and 40 K is of particular interest from radiological point of view, as they can form the basis of radiological assessments for the human population.…”
Section: Introductionmentioning
confidence: 99%
“…The 137 Cs was readily mixed with soil and by rain. However, the potential radiological impact on humans from such low levels of 137 Cs is insignificant (Adam et al 1998, Aarkrog et al 1997.…”
Section: Sample Nomentioning
confidence: 99%